2020
DOI: 10.4183/aeb.2020.275
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide Treatment Reduces Thyroid Gland Volume, but Has No Effect on the Size Of Thyroid Nodules

Abstract: Context.Exenatide is a Glucagon-like Peptide-1 receptor agonist, which is widely used for type 2 diabetes mellitus (T2DM). Limited and conflicting results are present about the effect of exenatide on the thyroid gland.Objective. The aim of this study was to evaluate the effect of exenatide treatment on structural and functional features of the thyroid gland in patients with T2DM.Design. The study was a prospective study, performed between 2015 and 2017. The laboratory values and thyroid ultrasonography feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…And, weight loss is associated with reduction in serum TSH levels 5‐7 . All the previous studies that evaluated the effect of treatment of people with type 2 diabetes and obesity with GLP‐1 RA therapies on thyroid function have demonstrated a significant reduction in serum TSH levels with no difference in FT4 or FT3 levels with GLP‐1 RA agents 7,19,20 . Compared to our analysis, however, these erstwhile studies included a smaller number of participants (ranging between 33 and 49), most had a shorter duration of follow‐up (ranging between 6 and 16 months), and did not include a comparator group.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…And, weight loss is associated with reduction in serum TSH levels 5‐7 . All the previous studies that evaluated the effect of treatment of people with type 2 diabetes and obesity with GLP‐1 RA therapies on thyroid function have demonstrated a significant reduction in serum TSH levels with no difference in FT4 or FT3 levels with GLP‐1 RA agents 7,19,20 . Compared to our analysis, however, these erstwhile studies included a smaller number of participants (ranging between 33 and 49), most had a shorter duration of follow‐up (ranging between 6 and 16 months), and did not include a comparator group.…”
Section: Discussionmentioning
confidence: 72%
“…[5][6][7] All the previous studies that evaluated the effect of treatment of people with type 2 diabetes and obesity with GLP-1 RA therapies on thyroid function have demonstrated a significant reduction in serum TSH levels with no difference in FT4 or FT3 levels with GLP-1 RA agents. 7,19,20 Compared to our analysis, however, these erstwhile studies included a smaller number of participants (ranging between 33 and 49), most had a shorter duration of follow-up (ranging between 6 and 16 months), and did not include a comparator group. One of these studies, that included 33 patients with type 2 diabetes and who were followed-up for 6 months, didn't find any significant relationship between reduction in body weight and serum TSH using univariate correlation analysis.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The literature suggests that GLP-1R activation may have an impact on thyroid hormone levels and, more generally, on thyroid function parameters, although the exact mechanism and outcomes are still being elucidated. However, several studies reported contrasting findings, with a decrease in thyroid-stimulating hormone (TSH) levels as a result of GLP-1R activation [ 39 , 40 , 41 ].…”
Section: Effect Of Glp-1 Ras On the Hypothalamus-pituitary-thyroid Axismentioning
confidence: 99%